Clinicodemographic Profile of Kidney Diseases in a Tertiary Hospital of Central Nepal, Chitwan: A Descriptive Cross-sectional Study - Ghimire, Madhav (JNMA J Nepal Med Assoc, 2020)
INTRODUCTION: Spectrum of kidney diseases differs significantly in developing and developed countries. However, there is no central registry regarding the nature of such diseases in Nepal and our center either. The study aims to know the clinicodemographic spectrum of kidney disease patients admitted to our hospital. METHODS: This study was a descriptive cross sectional study done in the department of Nephrology, College of Medical Sciences Teaching Hospital from May 2018 to April 219. Convenient sampling was done and all the consecutive kidney disease patients irrespective of their age, sex, and renal diagnosis were included in the study. Ethical approval was taken from the Institutional Review Committee of the college (reference number. 2016/COMSTH/IRC/049). Clinicodemographic profile of kidney diseases were studied using statistical package for the social sciences version 20 and were represented as mean, standard deviation, number, percentage and ratio. RESULTS: Out of a total of 829 patients, the commonest clinical syndrome and the histological patterns were end-stage renal disease 248 (29.9%) and IgA nephropathy 18 (20.7%) respectively. The mean age was 51.4±18.6 years. The commonest reason for hospitalization was sepsis 372 (44.8%). Males were 486 (58.6%) and females were 343 (41.4%). CONCLUSIONS: The commonest clinical presentation and the reason for admissions were end-stage renal disease and sepsis syndrome respectively.